Cloning and characterization of the Drosophila U7 small nuclear RNA - Dominski, Zbigniew (National Academy of Sciences, 2003)
Base pairing between the 5′ end of U7 small nuclear RNA (snRNA) and the histone downstream element (HDE) in replication-dependent histone pre-mRNAs is the key event in 3′-end processing that leads to generation of mature histone mRNAs. We have cloned the Drosophila U7 snRNA and demonstrated that it is required for histone pre-mRNA 3′-end processing in a Drosophila nuclear extract. The 71-nt Drosophila U7 snRNA is encoded by a single gene that is embedded in the direct orientation in an intron of the Eip63E gene. The U7 snRNA gene contains conserved promoter elements typical of other Drosophila snRNA genes, and the coding sequence is followed by a 3′ box indicating that the Drosophila U7 snRNA gene is an independent transcription unit. Drosophila U7 snRNA contains a trimethyl-guanosine cap at the 5′ end and a putative Sm-binding site similar to the unique Sm-binding site found in other U7 snRNAs. Drosophila U7 snRNA is ≈10 nt longer than mammalian U7 snRNAs because of an extended 5′ sequence and has only a limited potential to form a stem-loop structure near the 3′ end. The extended 5′ end of Drosophila U7 snRNA can base pair with the HDE in all five Drosophila histone pre-mRNAs. Blocking the 5′ end of the U7 snRNA with a complementary oligonucleotide specifically blocks processing of a Drosophila histone pre-mRNA. Changes in the HDE that abolish or decrease processing efficiency result in a reduced ability to recruit U7 snRNA to the pre-mRNA.